La «europeización» de decisiones de Derecho privado (Revista Española de Derecho Internacional, 2008)
Whereas the European Enforcement Order constitutes a unique legal system integrated by all the Members States (systematic dimension), this technique can be extended in the future to foster all the aims of the European Law, providing that the constitutional systems of the Members States are respected. Having regard to this system is, besides of integrated, a system of justice (axiological dimension), it has to respect essential values, mainly of judicial effective protection, which is increasingly influenced by the power of the Private Law subjects (they can apply for the certification of their private executive agreements as European Order and choose between recognition or European Order). Due to this integrated system has place within the European Area (spatial dimension), a correlation has to be established between the European Order Rules and the European Regulations on judicial jurisdiction and applicable Law, taking into account the influence of the systems of third States and the agreements signed with them.